Costos por procesos en el pilado de arroz y su efecto en la fijación de precios en el Molino Guadalupe S.A.C. – 2018 - Idrogo Soto, Kiara Yesabel (2019)
This research is based on the study of the company Molino Guadalupe S.A.C. Regarding the determination of costs, analyze how they influence each of the rice pile processes, in the pricing in the company with the purpose of proposing a model of Process Cost System to facilitate pricing reasonable and competitive in the milling sector. The study was carried out through an interview with the General Manager of the company Molino Guadalupe S.A.C. and a survey of the client farmers of the milling company, where it was determined that the company Molino Guadalupe S.A.C. It does not have a Process Cost System, which generates that the costs are calculated on uncertain bases and no real information is generated, based solely on the Market Price of the other mills in the Valley to be able to establish a price for the service provided. The research work showed that process costs have a positive effect since they play an essential role in the rice pile because they are a basic tool for pricing, allowing to establish the desired profit margin and a reasonable price and competitive, which will allow to face the competition for offering an adequate price that adjusts to the resources of the farmers. A Process Cost System was proposed, in which each of the costs incurred in the production process was detailed: reception, inspection and weighing, drying, storage, rice pile service, storage and sale, which allowed the Molino Guadalupe SAC; have better control and optimize resources efficiently so that management makes decisions with a clearer and safer projection.